Reviving Trade Routes : Evidence from the Maputo Corridor - Sequeira, Sandra; Hartmann, Olivier; Kunaka, Charles (World Bank, Washington, DC, 2015)
Most trade moves along a few high-density routes: the corridors. Improving their performance has emerged as a necessary ingredient for growth and integration into the regional and global economy. In Africa, this is recognized at the continental level, where program for infrastructure development in Africa (PIDA) has identified 42 corridors that should form a core network for regional integration and global connectivity. Several distinctive features appear to be necessary conditions for a successful corridor, namely (i) a combination of public and private investments to improve infrastructure, (ii) an institutional framework to promote and facilitate coordination, (iii) a focus on operational efficiency of the logistics services and infrastructure, and (iv) a proven economic potential. Reviewing the experience of an apparently successful corridor can help one learn the optimal mix and trade-offs among the ingredients and enable replication of success on other corridors. The lessons from the Maputo corridor can help the regional economic communities (REC), countries, corridor users, and development partners to better focus their corridor strategies to maximize economic growth. The present work focuses on three aspects of its revival: corridors as enablers of trade and economic development; improvement of logistics through investments and reforms; institutional framework adapted according to objectives.